Dispositional self‐compassion and responses to mood challenge in people at risk for depressive relapse/recurrence. (12th June 2018) - Karl, Anke; Williams, Matthew J.; Cardy, Jessica; Kuyken, Willem; Crane, Catherine
Abstract : This paper explores the relationship between dispositional self‐compassion and cognitive emotion regulation capacities in individuals with a history of depression. Study 1 ( n  = 403) established that self‐compassion was associated with increased use of positive and decreased use of negative strategies, with small to medium sized correlations. Study 2 ( n  = 68) was an experimental study examining the association between dispositional self‐compassion, use of cognitive emotion regulation strategies, and changes in mood and self‐devaluation in participants exposed to a negative mood induction followed by mood repair (mindfulness, rumination, silence). Individuals with higher levels of dispositional self‐compassion showed greater mood recovery after mood induction, and less self‐devaluation across the experimental procedure, independent of their mood‐repair condition or habitual forms of cognitive emotion regulation. These results suggest that self‐compassion is associated with more adaptive responses to mood challenges in individuals with a history of recurrent depression.